Effect of Zencore-Based Adaptive Learning on Numeracy Literacy in Mixed Arithmetic Operations among Fourth-Grade Students - Khairunnisa, Andini (International Conference on Elementary Education, 2025)
This study aims to analyze the effectiveness of the Zencore feature in the Zenius application as a form of adaptive learning to improve mathematics learning outcomes on the topic of mixed integer operations. A quasi-experimental design was employed, involving an experimental class that used Zencore and a control class that received conventional instruction. The research instruments included a pretest, posttest, and an observation sheet. The results showed a difference in the improvement of learning outcomes between the two classes. The experimental class demonstrated improvement in the medium category, while the control class showed improvement in the low category. These findings suggest that the Zencore feature supports students in understanding mixed integer operations at their individual learning pace.